A Search for Value Propositions for Small Food Firms - Otakanon, Burim; Ngmrojanavanich, Nattaya; v, Nongnuj; Gowanit, Chupun (International Journal of Supply Chain Management, 2020)
The value proposition has largely affected firms in the growth of the business. A firm needs to comprehend which needs are to be addressed in order to satisfy the market for the values created.  This paper is aimed at exploring the components of value that constitute the proposition. This profound question was investigated by the collection of interviews in the media achieved. The content analysis technique was employed to manipulate data. This research indicates that there are eight values that small food firms should consider in developing a value proposition. These eight values have a substantial impact on the decision making of the gatekeepers, which are standards, product quality, relationship, profitability, convenience, food and taste, communication, and experience. The value proposition acts as a gateway to the market. The interruption in the value proposition process perilously increases the risk of being a dead-ended product. The key managerial insight contributes by this paper is that the cascading of the value tiers reveals the novelty components of how the value proposition has been constructed.